2016
DOI: 10.1002/fuce.201500139
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of La0.6Sr0.4Co0.2Fe0.8O3–δ–Ce0.8Sm0.2O1.9 Cathodes on Coated and Uncoated Porous Metal Supports

Abstract: The degradation of composite LSCF-SDC cathodes on porous 430 stainless steel supports was investigated. Two degradation mechanisms were observed: a multi-layer oxide scale, believed to consist of Cr 2 O 3 and SrCrO 4 , formed at the support-cathode interface, and small amounts of chromium were detected within the cathodes. To reduce degradation, La 2 O 3 and Y 2 O 3 reactive element oxide coatings were deposited on the internal pore surfaces of the metal supports. The reactive element oxide coatings reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The present study is focused on the metal support microstructure; however, it has been previously shown that the durability of metal‐supported cathode‐first cells is compromised by the tendency of Cr to volatilize and redeposit at the pore surfaces in oxidizing conditions typical of an SOFC cathode compartment. Harris et al reported that the degradation rate during operation was reduced by depositing La 2 O 3 or Y 2 O 3 reactive element oxide coatings on the pores of the metal support, which significantly decreased the extent of volatilization of Cr and a correspondingly decreased rate of degradation of cell performance . In a separate study, the application of reactive element oxides such as La 2 O 3 and Y 2 O 3 was also shown to be effective in decreasing the oxidation rate of metal supports at high temperatures typical of SOFC operation .…”
Section: Resultsmentioning
confidence: 99%
“…The present study is focused on the metal support microstructure; however, it has been previously shown that the durability of metal‐supported cathode‐first cells is compromised by the tendency of Cr to volatilize and redeposit at the pore surfaces in oxidizing conditions typical of an SOFC cathode compartment. Harris et al reported that the degradation rate during operation was reduced by depositing La 2 O 3 or Y 2 O 3 reactive element oxide coatings on the pores of the metal support, which significantly decreased the extent of volatilization of Cr and a correspondingly decreased rate of degradation of cell performance . In a separate study, the application of reactive element oxides such as La 2 O 3 and Y 2 O 3 was also shown to be effective in decreasing the oxidation rate of metal supports at high temperatures typical of SOFC operation .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it avoids intimate contact between the cathode and bare stainless steel, for which accelerated Cr deposition in the cathode would be a concern. Recently, MS-SOFCs with the cathode instead applied to a presintered stainless steel substrate by plasma spray deposition have been investigated; this avoids interdiffusion between Fe and Cr from the stainless steel and Ni from the anode [6,7].…”
mentioning
confidence: 99%
“…Nonetheless, the increased cell temperature due to combustion would tend to accelerate SrZrO 3 interlayer formation. Lastly, Cr diffusion from the substrate into the functional layers of the cell is also a known degradation mode [61,62]. Cr and Fe migration have been observed from the substrate into an adjacent fuel electrode [62], which may explain degradation at 2000-4000 Hz in addition to 20-40 Hz.…”
Section: Short-term Durability Testingmentioning
confidence: 99%